Disruption of the LTD dialogue between the cerebellum and the cortex in Angelman syndrome model: a timing hypothesis - Cheron, Guy; Márquez-Ruiz, Javier; Kishino, Tatsuya; Dan, Bernard (Frontiers in Systems Neuroscience, 2014)
Angelman syndrome is a genetic neurodevelopmental disorder in which cerebellar functioning impairment has been documented despite the absence of gross structural abnormalities. Characteristically, a spontaneous 160 Hz oscillation emerges in the Purkinje cells network of the Ube3am-/p+ Angelman mouse model. This abnormal oscillation is induced by enhanced Purkinje cell rhythmicity and hypersynchrony along the parallel fiber beam. We present a pathophysiological hypothesis for the neurophysiology underlying major aspects of the clinical phenotype of Angelman syndrome, including cognitive, language and motor deficits, involving long-range connection between the cerebellar and the cortical networks. This hypothesis states that the alteration of the cerebellar rhythmic activity impinges cerebellar long-term depression (LTD) plasticity, which in turn alters the LTD plasticity in the cerebral cortex. This hypothesis was based on preliminary experiments using electrical stimulation of the whiskers pad performed in alert mice showing that after a 8 Hz LTD-inducing protocol, the cerebellar LTD accompanied by a delayed response in the wild type mice is missing in Ube3am-/p+ mice and that the LTD induced in the barrel cortex following the same peripheral stimulation in wild mice is reversed into a LTP in the Ube3am-/p+ mice. The control exerted by the cerebellum on the excitation vs inhibition balance in the cerebral cortex and possible role played by the timing plasticity of the Purkinje cell LTD on the spike–timing dependent plasticity (STDP) of the pyramidal neurons are discussed in the context of the present hypothesis.